2021
DOI: 10.1080/15378020.2021.1883213
|View full text |Cite
|
Sign up to set email alerts
|

Understanding eating behaviors of foreign residents: A case of Turkey

Abstract: Eating behaviors have been investigated for many years. The current research sheds light on the relationship between external (EXT), restrained (RES), emotional (EMO), and attitude toward Turkish cuisine (At_TC) in terms of foreign residents. A survey was conducted on foreign residents living in Turkey, by examining the extent to which Dutch Eating Behavior Questionnaire (DEBQ) constructs (EXT, RES, EMO) of At_TC can be predicted by utilizing a partial least square algorithm. Results show significant relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 105 publications
(136 reference statements)
0
1
0
Order By: Relevance
“…The end result was that many students in this study reported becoming either over-weight or scrawny as a result of either skipping meals (especially breakfast) or embracing a malnourished diet. Psychological factors and emotions have been found to influence what people eat (Levitan and Davis, 2010;Sezgin and Tanrisevdi, 2021). In particular, food consumption was said to be a function of the state of mind; the higher the level of negativity, the greater the quantity of food eaten (Evers et al, 2013).…”
Section: Changes In Eating Habitsmentioning
confidence: 99%
“…The end result was that many students in this study reported becoming either over-weight or scrawny as a result of either skipping meals (especially breakfast) or embracing a malnourished diet. Psychological factors and emotions have been found to influence what people eat (Levitan and Davis, 2010;Sezgin and Tanrisevdi, 2021). In particular, food consumption was said to be a function of the state of mind; the higher the level of negativity, the greater the quantity of food eaten (Evers et al, 2013).…”
Section: Changes In Eating Habitsmentioning
confidence: 99%